Core–shell graphene oxide–polymer hollow fibers as water filters with enhanced performance and selectivity. (10th December 2020) - Kovtun, Alessandro; Bianchi, Antonio; Zambianchi, Massimo; Bettini, Cristian; Corticelli, Franco; Ruani, Giampiero; Bocchi, Letizia; Stante, Francesco; Gazzano, Massimo; Marforio, Tainah Dorina; Calvaresi, Matteo; Minelli, Matteo; et al.
Abstract : Graphene oxide (GO) coated hollow fiber filters could selectively capture three target water contaminants. The separation mechanism relies on synergic physical size exclusion and intercalation of solute 6 molecules between GO layers Abstract : Commercial hollow fiber filters for micro- and ultrafiltration are based on size exclusion and do not allow the removal of small molecules such as antibiotics. Here, we demonstrate that a graphene oxide (GO) layer can be firmly immobilized either inside or outside polyethersulfone–polyvinylpyrrolidone hollow fiber (Versatile PES®, hereafter PES) modules and that the resulting core–shell fibers inherits the microfiltration ability of the pristine PES fibers and the adsorption selectivity of GO. GO nanosheets were deposited on the fiber surface by filtration of a GO suspension through a PES cartridge (cut-off 0.1–0.2 μm), then fixed by thermal annealing at 80 °C, rendering the GO coating stably fixed and unsoluble. The filtration cut-off, retention selectivity and efficiency of the resulting inner and outer modified hollow fibers (HF-GO) were tested by performing filtration on water and bovine plasma spiked with bovine serum albumin (BSA, 66 kDa, ≈15 nm size), monodisperse polystyrene nanoparticles (52 nm and 303 nm sizes), with two quinolonic antibiotics (ciprofloxacin and ofloxacin) and rhodamine B (RhB). These tests showed that the microfiltration capability of PES was retained by HF-GO, and in addition the GO coating can capture the molecular contaminants while letting through BSA and smaller polystyrene nanoparticles. Combined XRD, molecular modelling and adsorption experiments show that the separation mechanism does not rely only on physical size exclusion, but involves intercalation of solute molecules between the GO layers.